Environmental and Behavioral Determinants of Filariasis Among Adolescents in North Sumatra Province: A Cross-sectional Analysis of National Health Survey Data - Putra Apriadi Siregar; Rani Elviyanti Siregar; Desty Adinda; Muhammad Rezebri; Apriliani Apriliani; Prima Yanti Siregar; Sabila Pratiwi (Poltekkes Kemenkes Surabaya, 2026)
Lymphatic filariasis remains a public health problem in North Sumatra Province, but research focusing on adolescents as a “hidden reservoir” in the transmission chain is still very limited. Most previous studies have focused on adult populations or small endemic clusters, thereby neglecting the specific risk dynamics in younger age groups. This study aims to analyze environmental and behavioral determinants that influence the incidence of filariasis specifically in the adolescent population in North Sumatra using provincial-level data. We conducted a cross-sectional analytical study using secondary data from the 2018 Indonesian Basic Health Survey (Riskesdas). A total of 13,860 individuals were included from all 33 districts/cities in North Sumatra using a census block sampling method. The dependent variable was filariasis incidence. Independent variables included demographic characteristics, ventilation adequacy, waste management, and mosquito prevention practices (e.g., repellent use, insecticide-treated nets). Data analysis was performed using chi-square tests and binary logistic regression to determine significant associations, with statistical significance set at p < 0.05. Among households surveyed, only 50.2% had adequate bedroom ventilation, while 91.4% had uncovered garbage, serving as potential mosquito breeding grounds. Insecticide-treated net usage was low (38%), and nearly half of the adolescents did not use repellents. Garbage disposal was significantly associated with filariasis incidence in all demographic groups (p < 0.001). Repellent use showed a protective association among rural residents (p = 0.02) and females (p = 0.018). Homes equipped with window screens had lower infection rates. The risk of filariasis in adolescents in North Sumatra is predominantly triggered by the failure of the household waste management system and the lack of physical protection of residential ventilation. The insignificance of mosquito net use confirms that transmission among adolescents occurs more through interaction with vector habitats outdoors or during nocturnal activities. Health interventions should shift from mass treatment to improving environmental sanitation and educating adolescents on adaptive self-protection behaviors.